Academic foundations of hospitality management research with an emerging country focus: A citation and co-citation analysis. (February 2015) - Köseoglu, Mehmet Ali; Sehitoglu, Yasin; Craft, Jana
Abstract: This study explores the academic foundations of hospitality management research within an emerging country using bibliometric analysis – citation and co-citation analysis. Turkey was chosen as a starting point to assess existing research within an emerging country framework because of the large impact of tourism and hospitality (T/H) on the economy and increasing amount of academic research in the field. A total of 76 hospitality management research articles from 1992 to 2013 were found in leading international T/H journals indexed by SSCI. Findings showed that over one-half of the research comes from publications engaging outside of the T/H field. Patterns emerged between T/H and management, marketing and psychology fields that indicated evolving maturity in the research. An intense dependency on supporting journals for substantiation existed and intra-disciplinary maturity was weak, but growing. Accordingly, referring to the findings related to the study, the article discusses limitations of the study and future steps.